Analise van die opbou, argumentasiegang en pragmatiek van die Galatebrief: ’n meer gedetailleerde oorsig - Toit, Andries Bernardus du (Verbum et ecclesia, 1991)
Analysis of the structure, argument and pragmatics of Galatians: a more detailed overview Following on a previous article in this journal a more detailed overview is presented, describing the structure, argument and pragmatic thrust of Galatians down to the level of its constituent pericopes and paragraphs. Although Galatians is in more than one respect a highly emotional document, its overall pattern displays strong cohesion and a consistent persuasive focus.